The Effect Of Pumpkin Seed (Cucurbita sp.) And Sesame Seed (Sesamum indicum L.) Addition On The Sensory, Nutritional, And Physical Characteristics Of Almond Csrispy - Sabrina Eka Salsabila; Siti Fathonah (Universitas Negeri Padang, 2026)
Pumpkin seeds and sesame seeds are local food ingredients with the potential to improve the sensory quality and nutritional value of almond crispy. This study aimed to analyze the effect of pumpkin seed and sesame seed addition on the acceptability, nutritional content, and physical characteristics of almond crispy. A Completely Randomized Design (CRD) with one factor and three levels of seed addition (30%, 40%, and 50%) was employed. Acceptability was evaluated by 40 semi-trained panelists using a 9-point hedonic scale for color, aroma, taste, texture, and overall acceptability. Nutritional content was analyzed through moisture and protein determination, while physical characteristics were evaluated through color and texture measurements. The results showed that the addition of pumpkin seeds and sesame seeds significantly affected all acceptability attributes (p<0.05). The 50% addition level achieved the highest acceptability scores for color (8.28), aroma (8.60), taste (8.13), texture (8.35), and overall acceptability (8.68). Moisture content ranged from 1.62% to 1.98%, while protein content ranged from 14.67% to 15.51%. All formulations complied with the quality requirements for cookies specified in the Indonesian National Standard (SNI 2973:2011), namely a maximum moisture content of 5% and a minimum protein content of 5%. The 40% addition level produced the highest hardness value (353.5 g), whereas the 50% addition level was selected as the best formulation based on its superior acceptability and higher protein content. Therefore, the addition of 50% pumpkin seeds and sesame seeds has the potential to improve the sensory quality and nutritional value of almond crispy.